Potent anti-cervical cancer activity: Synergistic effects of Thai medicinal plants in recipe N040 selected from the MANOSROI III database - Worapong Kitdamrongtham (2018)
Ethnopharmacological relevances One of the prestigious Thai/Lanna folklore wisdoms is the medicinal plant recipes. Thai/Lanna medicinal plant recipe database MANOSROI III has been developed by Prof. Dr. Jiradej Manosroi. It consists of over 200,000 recipes covering all diseases including cancer. Aim of this study To investigate the in vitro and in vivo anti-cervical cancer activity and the active constituents of the Thai medicinal plant recipe N040 selected from the MANOSROI III database. Materials and methods The extracts of recipe N040 and single medicinal plants in the recipe were prepared by hot water and methanol extraction, respectively. The n-hexane, ethyl acetate (EtOAc), n-butanol (n-BuOH) and water fractions of Caesalpinia sappan, the plant which showed the highest anti-proliferative activity were prepared by liquid-liquid partition extraction. The fraction which showed the highest anti-proliferative activity was further isolated for active constituents. Anti-proliferative activity of recipe N040, methanolic extracts, fractions of Caesalpinia sappan and brazilin, an active constituent on HeLa cell were investigated using sulforhodamine B (SRB) assay. Anti-oxidative activities including free radical scavenging and metal ion-chelating activities, as well as the phenolic and flavonoid contents of these fractions were also determined. The in vivo anti-cancer activity of recipe N040 on HeLa cell xenograft and the subchronic toxicity were performed in nude mice and rats, respectively. Results and conclusions N040 showed the potent in vitro anti-proliferative activity on HeLa cell with the IC 50 value of 0.11 μg/ml. Phytochemicals detected in the plants were steroids/triterpenoids, tannins, flavonoids, saponins and alkaloids. For the single plant, methanolic extract of Caesalpinia sappan gave the highest anti-proliferative activity with the IC 50 of 33.46 μg/ml. EtOAc fraction of Caesalpinia sappan showed the highest anti-proliferative and free radical scavenging activities with the IC 50 and SC 50 of 17.81 and 21.95 μg/ml which were 1.88 and 0.83 folds of its methanolic extract and ascorbic acid, respectively. Poor metal chelating activity (MC 50 > 500 μg/ml) was observed in methanolic extract and all fractions. The highest phenolic and flavonoid contents were observed in the methanolic extract. Brazilin, the known compound isolated from the EtOAc fraction exhibited potent anti-proliferative activity with the IC 50 of 0.28 μg/ml which was higher than its methanolic extract and EtOAc fraction of 119.50 and 63.61 folds, respectively, but only 0.39 fold of the recipe extract N040. The tumor size of the HeLa cell xenograft nude mice treated with the recipe N040 at the dose of 44.50 mg/kg body weight per day was significantly smaller (p < 0.05) than that of the control with the relative tumor weight inhibition of 57.23% which was 0.65 fold of cisplatin. In the subchronic toxicity study, N040 given orally at the dose of 1000 mg/kg body weight per day for 90 days showed no alteration in body weight gain, hematology [except the increase mean corpuscular hemoglobin (MCH) in the treated male rats] and clinical blood chemistry (except the increase blood glucose in the treated male rats) both in female and male rats. Only minor lesions of the organs including lung, liver, kidney and small intestine were observed in both sexes. This study has demonstrated the synergistic effect of the plants composed in the recipe which resulted in the potent anti-cancer activity and confirmed the traditionally use of the recipe N040. In addition, this study has also suggested the compound brazilin isolated from Caesalpinia sappan for its high potential to be further investigated as a novel anti-cervical cancer drug. © 2013 Elsevier Ireland Ltd.